2018
DOI: 10.1038/s41390-018-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal intermittent hypoxemia events are associated with diagnosis of bronchopulmonary dysplasia at 36 weeks postmenstrual age

Abstract: Background: Bronchopulmonary dysplasia (BPD) is a chronic lung disease and major pulmonary complication after premature birth. We have previously shown that increased intermittent hypoxemia (IH) events have been correlated to adverse outcomes and mortality in extremely premature infants. We hypothesize that early IH patterns are associated with the development of BPD. Methods: IH frequency, duration, and nadirs were assessed using oxygen saturation (SpO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…Di reported that preterm infants with increased oxygen and frequent intermittent hypoxia (IH) events during only the first 3 days of age were commonly on asthma medication at 2 years and total apnoea days were associated with neurodevelopmental impairments (Janvier et al, 2004). Raffay et al (2019) reported an association between frequent, longer and less severe IH events, in addition to oxygen supplementation and respiratory pressure support within the first 26 days of life, and the incidence of bronchopulmonary dysplasia at 36 weeks' postmenstrual age. There is growing evidence to suggest a sex-specific developmental trajectory and thereby sex-dependent responses to treatment and long-term outcomes, with male sex being recognized as a significant factor in poor respiratory outcomes in preterm infants (Farrell & Wood, 1976;Wiswell, Tuggle, & Turner, 1990).…”
Section: Clinical Approaches To Preterm Respiratory Carementioning
confidence: 99%
See 1 more Smart Citation
“…Di reported that preterm infants with increased oxygen and frequent intermittent hypoxia (IH) events during only the first 3 days of age were commonly on asthma medication at 2 years and total apnoea days were associated with neurodevelopmental impairments (Janvier et al, 2004). Raffay et al (2019) reported an association between frequent, longer and less severe IH events, in addition to oxygen supplementation and respiratory pressure support within the first 26 days of life, and the incidence of bronchopulmonary dysplasia at 36 weeks' postmenstrual age. There is growing evidence to suggest a sex-specific developmental trajectory and thereby sex-dependent responses to treatment and long-term outcomes, with male sex being recognized as a significant factor in poor respiratory outcomes in preterm infants (Farrell & Wood, 1976;Wiswell, Tuggle, & Turner, 1990).…”
Section: Clinical Approaches To Preterm Respiratory Carementioning
confidence: 99%
“…Raffay et al. () reported an association between frequent, longer and less severe IH events, in addition to oxygen supplementation and respiratory pressure support within the first 26 days of life, and the incidence of bronchopulmonary dysplasia at 36 weeks’ postmenstrual age. There is growing evidence to suggest a sex‐specific developmental trajectory and thereby sex‐dependent responses to treatment and long‐term outcomes, with male sex being recognized as a significant factor in poor respiratory outcomes in preterm infants (Farrell & Wood, ; Wiswell, Tuggle, & Turner, ).…”
Section: Preterm Physiologymentioning
confidence: 99%
“…It is known that hyperoxia induces free radical injury but there is evidence that desaturation and reoxygenation can contribute to pro-oxidant signaling [10-12]. In extremely preterm infants, intermittent hypoxemia (IH) events are prolific [13] and are associated with multiple adverse outcomes [14-17]. Thus, the potential for IH to induce oxidative stress and reduce antioxidant activation resulting in free radical damage may be a causal pathway in neonatal morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively short respiratory pauses may precipitate O2 desaturation, bradycardia, and pulmonary hypertension. This can induce retinopathy of prematurity (ROP), sleep disordered breathing, and neurodevelopmental delay (36, 37).…”
Section: Introductionmentioning
confidence: 99%